2020
DOI: 10.1088/1755-1315/462/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air temperature and velocity on the drying characteristics and product quality of Clinacanthus nutans in heat pump dryer

Abstract: Fresh Clinacanthus nutans (C. nutans) leaves were dried using a heat pump dryer where the effects of drying temperature (40, 50, and 60°C) and air velocity (2.5, 3.0, and 3.5 m/s) on the drying characteristics and product quality were investigated. Data showed that higher air temperature and velocity resulted in a shorter drying duration. At higher air temperature and velocity, more heat was supplied to the C. nutans leaves, which increased the drying force for moisture evaporation and subsequently led to fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…Segundo Tajudin et al (2019), a degradação da vitamina C não se dá tão somente pela exposição a elevada temperatura, como também pelo tempo de exposição. Tendo em vista que a 50 ºC o tempo de secagem foi 50% maior, isso explica esse comportamento, também observado por Norhaida et al (2020).…”
Section: Resultsunclassified
“…Segundo Tajudin et al (2019), a degradação da vitamina C não se dá tão somente pela exposição a elevada temperatura, como também pelo tempo de exposição. Tendo em vista que a 50 ºC o tempo de secagem foi 50% maior, isso explica esse comportamento, também observado por Norhaida et al (2020).…”
Section: Resultsunclassified
“…At higher inlet air velocities, the volume of sago waste in the FBD decreases rapidly. It is supported by a study by Norhaida et al (2020), which found that increased velocities led to reduced drying times.…”
Section: Effect Of Air Velocity On Moisture Contentmentioning
confidence: 68%